Hufu Tongbian Guasha in the treatment of bloating and constipation in a patient with cholestatic jaundice (虎符铜砭刮痧改善1例胆汁淤积性黄疸患者腹胀和便秘的护理) - WANG Rui (王蕊); HU Jinrui (胡金瑞) (中西医结合护理)
This paper summarized the nursing practice of Hufu Tongbian Guasha in the treatment of bloating and constipation in a patient with cholestatic jaundice. Patient received a comprehensive treatment including liver protection, lowering transaminase and inhibiting gastric acid secretion. Based on the theory of Traditional Chinese Medicine syndrome differentiation, the Hufu Tongbian Guasha therapy was carried out in combination with nursing interventions on daily living, dietary and emotion of the patient. After 12 days of treatment of nursing by syndrome differentiation, the clinical symptoms such as pain, bloating and constipation (dry stool) was relieved. The application of Traditional Chinese Medicine nursing also helps to relieve the anxiety of the patient during treatment. (本文总结虎符铜砭刮痧改善1例胆汁淤积性黄疸患者腹胀和便秘的护理经验。患者住院期间在保肝、降酶、抑酸护胃等常规治疗的基础上, 基于中医四诊合参进行护理评估, 提出辨病辨证; 在中医特色理论指导下, 辨证应用虎符铜砭刮痧疗法, 并且在生活起居、饮食、情志等方面进行辨证施护。经过12 d的治疗及辨证施护, 患者舌面疼痛、纳呆、腹胀、大便干结的症状得到有效改善, 焦虑情绪得到缓解。)